Assessment of daleh swidden agriculture as an innovative alternative to conventional swidden under conditions of external pressure on local forest management in Kalimantan, Indonesia - NDAN IMANG; RUJEHAN RUJEHAN; NELLA NAOMI DUAKAJU (Biodiversitas Journal of Biological Diversity, 2018)
Imang N, Rujehan, Duakaju NN. 2018. Assessment of daleh swidden agriculture as an innovative alternative to conventional swidden under conditions of external pressure on local forest management in Kalimantan, Indonesia. Biodiversitas 19: 840-848. Swidden agriculture is still an important livelihood for millions of people in the tropics. In Kalimantan Island of Indonesia, swidden agriculture is currently facing many external pressures such as massive expansion of oil palm plantations, concession for industrial plantations, and non-availability of financial and political support from the government. The above external pressures which ignore local wisdom in forest and land management have reduced the land available for swidden agriculture. The external pressures, in turn, have shortened the cycle of swidden agriculture and decreased the productivity of swidden agriculture. The objectives of the present study are to assess socio-cultural and economic aspects of the innovative daleh agriculture as an alternative to conventional swidden agriculture under these conditions. The study was conducted in an indigenous Bahau Dayak community of East Kalimantan, Indonesia. Twenty swiddeners and 6 other key informants were interviewed for data collection. Research findings confirm that the expansion of oil palm plantations has ignored the wisdom in forest and land management, in general, and caused pressure on swidden agriculture, in particular. Under such pressures, daleh swidden agriculture may be effectively practiced because it can increase land productivity and is also culturally acceptable. Further, financial and facilitation support from district government is needed to improve the practice of swidden agriculture in the study area.